Moda: um olhar antropológico - Silva, Fernanda de Paula (1998)
This work proposes an incursion into the elements which envolve the various areas of Fashion considering it as a language, and its purpose is to offer facts on the cultural and anthropological aspects of Brazil from the modernism until today. After an investigation of our history through the important industry of Fashion and research which envolves two major Brazilian stylists: Marília Valls and Mena Fiala, I have stressed out the necessity of a greater professionalism and help towards this industry. It is noticeable that a Brazilian style in fashion emerges together with serious and creative professionals. Through this artistic and ethnographic study, I discovered the fascinating way in which art stimulates our perception, develops our level of knowledge and conscience, besides the fact that it significantly improves our quality of life. Questions like lifestyle, colours fabrics, professionalism, are important to all human beings. Oddly enough those subjects send us back once again to a language, the language of Fashion.